Training on Salted Egg Production Utilizing Local Potential in Cibodas Village, Tanara Subdistrict, Serang, Banten - Kurniasih Dwi Astuti; Rudi Zulfikar (EQUATOR SINAR AKADEMIA, 2023)
One of the objectives of this research activity is to increase the potential contained in micro business activities in the community in one of the villages in Pandeglang district, Banten. Lack of knowledge and skills in keeping up with the times makes most business actors unable to compete in potential markets. Based on this, socialization activities and product packaging training were carried out for business actors who use local potential in Banten, especially in Pandeglang Regency, Curugciung Village to be precise. The results of the research show that the development of packaging knowledge and skills by business actors utilizing local potential is increasing rapidly. Apart from being a challenge for the business world, it is also a huge opportunity and potential for improving the economy and business. Business actors must be able to keep up with changing trends by utilizing information technology to encourage business activities while increasing competitiveness.